pull down to refresh
2/3
\frac{T^3-1}{T^3+1} = \left( \frac{T-1}{T+1} \right) \left( \frac{T^2+T+1}{T^2-T+1} \right)
\prod_{n=2}^{T} \frac{n^3-1}{n^3+1} = \frac{2}{3} \left( \frac{T^2+T+1}{T^2+T} \right)
T \rightarrow \infty
T=2
\prod_{n=2}^{T} \frac{n^3-1}{n^3+1} = \left( \prod_{n=2}^{T-1} \frac{n^3-1}{n^3+1} \right) \left( \frac{T^3-1}{T^3+1} \right)
= \frac{2}{3} \left( \frac{(T-1)^2 + (T-1) + 1}{(T-1)^2 + (T-1)} \right) \left( \frac{T-1}{T+1} \right) \left( \frac{T^2+T+1}{T^2-T+1} \right)
= \frac{2}{3} \left( \frac{T^2 - T + 1}{T^2-T} \right) \left( \frac{T-1}{T+1} \right) \left( \frac{T^2+T+1}{T^2-T+1} \right)
= \frac{2}{3} \left( \frac{T^2+T+1}{T^2+T} \right)
2/3
2/3
in the limit asT \rightarrow \infty
T=2
.